PENERAPAN TEKNIK RATIONAL EMOTIVE BEHAVIORAL THERAPY (REBT) UNTUK MENINGKATKAN SELF ESTEEM SISWA SMAN 1 PALOPO - Arman Bin Anuar; Ainul Fahmi; Muhammad Irham Zainuri; Sabbi Hisma (Educouns Journal: Jurnal Pendidikan dan Bimbingan Konseling, 2022)
The purpose of this study was to describe the level of self-esteem of students before and after the treatment of the Rational Emotive Behavioral Therapy (REBT) technique and to determine the effect of the REBT technique on students' self-esteem. This study used a pre-experimental study method with the one-group pretest-posttest design. The subjects of this study were 10 students of class XI at SMAN 1 Palopo for the academic year 2021/2022, which were determined by purposive sampling technique. Data collection was obtained using observation and the Self Esteem scale. The results showed that the level of self-esteem of students before being given treatment was in the low category, and after being given treatment was in the high category, and the REBT technique had a positive effect on students' self-esteem.